Nomogram for Preoperative Estimation of Orbit Invasion Risk in Periocular Squamous Cell Carcinoma - Xie, Minyue; Yu, Jie; Li, Lunhao; Jia, Renbing; Song, Xin; Wang, Yefei; Fan, Xianqun (Frontiers in Oncology, 2020)
Importance. Orbital invasion occurs in some periocular squamous cell carcinoma (SCC), compromising surgical outcomes and prognosis of patients. To date, however, there are no validation studies on clinical features related to orbit invasion in patients with periocular SCC. Objective. To explore clinical features that may be associated with orbital invasion and build a model for predicting the risk of orbit invasion. Design, Setting, and Participants. In this retrospective mono-center case-control study, 90 patients with periocular SCC treated in Ninth People's Hospital Shanghai Jiao Tong University School of Medicine from January 2005 to August 2019. Case is defined as SCC patient with orbit invasion before operation. Exposure is defined as different sites of lesion. Main Outcomes and Measures. Clinical features including time to relapse after surgery was collected. Multivariate logistic regression analysis was applied to identify independent risk clinical features associated with orbit invasion, which was then incorporated into a nomogram. Results. Of the 90 patients included in this study, 33 patients (36.7%) had orbit invasion. 14 of the 33 orbit invasive patients had local recurrence, while 11 of 57 orbit non-invasive patients had local recurrence, suggesting that orbit invasion is a risk factor for local recurrence. The multivariate binary logistic regression indicated that the lesions at the medial canthus (Odds ratio [OR], 5.024, 95%CI, 1.409-17.912, P = 0.013), the age at diagnosis (10-year intervals; OR, 0.590, 95%CI, 0.412-0.844, P = 0.004) and bleeding in the lesion (OR, 3.480, 95%CI, 1.254-9.660, P = 0.017) were three preoperative clinical features significantly associated with orbital invasion. Conclusion. For periocular SCC, lesions at the medial canthus, younger age of the patients at diagnosis and bleeding in the lesion were three main clinical features associated with orbit invasion. The risk score model for orbital invasion can act as a supportive tool for optimized clinical evaluation and treatment decisions.